Espaço Movimento: Physical exercise program as prevention strategy in supplementary care - Valéria Cristina de Faria; Isabella Carolina Silva Pereira; Maysa Araujo Carvalho; Emanuel de Almeida Lima; Robson da Silva Miranda; Guilherme de Azambuja Pussieldi; Afonso Timão Simplício (Revista Brasileira de Atividade Física e Saúde)
The aim of this study was to describe a program of health promotion and prevention of risks and diseases, developed by a health plan provider by means of results achieved and activities since its inception. To demonstrate the results, active and retired employees of UFV Campus Florestal and their dependents were selected, enrolled with this provider, to attend Espaço Movimento in two groups: gym (GG) and walking/running (WRG). All were submitted to anthropometric and mood profile evaluation, and a flexibility test at baseline and every six months; VO2max was assessed only for WRG. Submitted to 12 months of intervention, GG was composed of 45 participants (25 male), with mean age 46.1 ± 15.7 years. The WRG was subjected to six months of intervention, and composed of 12 participants (10 females), with mean age 42.8 ± 13.8 years. The logical model from 2013 to 2015 was used to present the activities. Results of both groups showed significant improvements in levels of physical fitness, anthropometric variables and mental health. Between the years 2013 and 2015, three annual events were offered to the community of Florestal, including a wider range of age, from children to seniors. Therefore, the proposal of the Espaço Movimento initiative seems to be innovative in the supplementary care and demonstrates effectiveness on the observed results.